Antecedencje konfliktu arabsko-izraelskiego - Lorenc, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The Author was prompted to ponder the origins of the Arab – Israeli conflict by the over-fifty-year-long danger posed to international safety by the instability in the Middle East. It has inspired an analysis of the historical, political, legal and international conditions that led to the reconstruction of the territorial status quo and the foundation of the Israeli State in 1948.